Dictionary of Labour Biography
XV, 320 p. 1 illus.
Keywords: The Dictionary of Labour Biography has an outstanding reputation as a reference work for the study of nineteenth and twentieth century British history. Volume XV maintains this standard of original and thorough scholarship. Each entry is written by a specialist drawing on an array of primary and secondary sources. The biographical essays engage with recent historiographical developments in the field of labour history. The scope of the volume emphasises the ethnic and national diversity of the British labour movement and neglected political traditions. .